The Participation within Indigenous Land management: Developments and Challenges of Indigenous Communities Protection - Gde Made Swardhana; Suviwat Jenvitchuwong (Lembaga Contrarius Indonesia, 2023)
In customary law communities, established land has a deep meaning and is integral to cultural identity and social life. However, customary land rights often face serious problems. This study aims to analyze the protection of customary land rights in Indonesia and Thailand, identify the factors causing the problem, and describe the latest developments in efforts to protect these rights. This study focuses more on normative legal research. The normative juridical method is intended to explain various laws and regulations related to the mechanism for recognizing customary law communities with a statutory approach. The result of this research is a list of factors that influence the problem of protecting customary land rights in Indonesia and Thailand, such as the existence of legal dualism in land management, conflicts of interest between indigenous peoples and the state, and unclear boundaries of customary land territories. Then, the impact of the problematic protection of customary land rights on customary law communities is legal uncertainty regarding the protection of customary land, a decline in the welfare of customary law communities, and inequality and discrimination against indigenous and tribal peoples.